2012
DOI: 10.1016/j.cyto.2012.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines in vitro production are associated with Ala16Val superoxide dismutase gene polymorphism of peripheral blood mononuclear cells

Abstract: Obesity is considered a chronic low-grade inflammatory state associated with a chronic oxidative stress caused by superoxide production (O(2)(-)). The superoxide dismutase manganese dependent (SOD2) catalyzes O(2)(-) in H(2)O(2) into mitochondria and is encoded by a single gene that presents a common polymorphism that results in the replacement of alanine (A) with a valine (V) in the 16 codon. This polymorphism has been implicated in a decreased efficiency of SOD2 transport into targeted mitochondria in V alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 18 publications
1
28
0
1
Order By: Relevance
“…These results suggest that superoxide imbalance associated to V allele (VV or AV) could to be related to inflammatory plasmatic biomarkers. The result corroborates the in vitro study performed by Montano et al [22] that evaluated cytokines production by human peripheral blood mononuclear cells (PBMCs) carrier's different Ala16Val-SOD2 genotypes and found higher levels of proinflammatory cytokines in VV-PBMCs when compared to AA-PBMCs.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results suggest that superoxide imbalance associated to V allele (VV or AV) could to be related to inflammatory plasmatic biomarkers. The result corroborates the in vitro study performed by Montano et al [22] that evaluated cytokines production by human peripheral blood mononuclear cells (PBMCs) carrier's different Ala16Val-SOD2 genotypes and found higher levels of proinflammatory cytokines in VV-PBMCs when compared to AA-PBMCs.…”
Section: Discussionsupporting
confidence: 80%
“…Previously, Montano et al [14] described positive association between VV genotype and obesity and other studies also described association with hypercholes-terolemia [15], diabetes or diabetic cardiovascular diseases [16,17] diabetic nephropathy [18] and diabetic retinopathy [19], elevate plasmatic oxided-LDL levels mainly in diabetic patients [20], elevate also lipid peroxidation, protein carbonylation [10,21] and proinflammatory-cytokines (IL-1β, IL-6, TNFα and Igɣ) [22].…”
Section: Introductionmentioning
confidence: 99%
“…gastric, lung, prostate, bladder and breast, to diabetes type I, nephropathy, chronic kidney disease, and to chemotherapy responses. The Ala16Ala genotype is generally associated with a protective effect, yet important differences are described in the literature, which indicates a complex role for the presence of risk allele C. Also, it has been suggested that SOD2 16Val variant is associated with an increased production of pro-inflammatory cytokines [43], and that its expression can be modulated through NF-kB binding to the promoter region of the gene [44]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the altered Mn-SOD variant increases the risk of oxidative stress associated with various pathologies, including diabetic microvascular disease (Chistyakov et al, 2001;Lee and Choi, 2006;Eras-Erdogan et al, 2009;Chen et al, 2012). Mn-SOD may be the most important member of the SOD family; therefore, people presenting Mn-SOD gene mutations are subjected to lower Mn-SOD efficiency and might be more prone to complications (Kariž et al, 2012;Montano et al, 2012). In our study, we found that the Mn-SOD CC genotype may protect against the development of complications in Tunisian T2D.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed a significant association of the T47C C allele of Mn-SOD with reduced risk of diabetic microvascular complications including diabetic nephropathy, diabetic retinopathy, and diabetic polyneuropathy in dominant, recessive, and codominant models (Tian et al, 2011). The SODs are a class of enzymes involved in the detoxification of superoxide into hydrogen peroxide (Montano et al, 2012). Three major isoforms of SOD have been identified according to their tissue location and transition metals.…”
Section: Introductionmentioning
confidence: 99%